Chaotic Effect of Coal Consumption on Economic Growth in the USA - Bildirici, Melike E.; Sonustun, Fulya Ozaksoy (AMER INST PHYSICS, 2018)
In this study, we attempt to test chaotic behavior of selected the variables and to determine chaotic relation between economic growth and coal consumption for the period from January, 1973 to March, 2018 in the USA by using Largest Lyapunov Exponents, Chaotic Causality perspectives. In this regard, firstly, it is aimed to identify nonlinear pattern of economic growth and coal consumption by BDS test. And secondly, it is purposed to determine chaotic behaviour of the analyzed series by Lyapunov Exponent. Further, chaotic causality is analyzed for this period. The analysis results demonstrate that coal consumption fluctuations have crucial effects on the USA's economic growth in the long term.
Keywords: Physics